LEXICAL AND CONTEXTUAL MEANINGS IN “BILLBOARD GLOBAL 200” TOP 1 SONG LYRICS OF 2024: PEDAGOGICAL IMPLICATION - Wimar Amalia, Shabrina; Suwandi, Suwandi; Musarokah, Siti (EDU RESEARCH, 2024)
This article aims to identify the lexical and contextual meanings in “Billboard Global 200” Top 1 song lyrics of 2024 and to explain the implementation of lexical and contextual meanings for teaching English as a foreign language. The researchers selected three songs that Top 1 in "Billboard Global 200" of 2024. This study is needed as a song becomes interesting to listen to, but often the instruments cause a misunderstanding, and even listeners do not realize the true lyrical meaning that the songwriter wants to convey. The qualitative research and descriptive approach are used as the methodology for analyzing lexical and contextual meanings. In this study, the researchers found thirty-five findings contained lexical and contextual meanings in selected three song lyrics. In detail, there were six words/ phrases and one expression in the Beautiful Things song lyric; seven words/ phrases and five expressions in the We Can’t Be Friends (Wait for Your Love) song lyric; and three words/ phrases and thirteen expressions in the Too Sweet song lyric. Furthermore, lexical and contextual meaning analysis in “Billboard Global 200” song lyrics can be used as an alternative to teaching English as a foreign language to enhance reading comprehension and writing ability. Therefore, the researchers gave teaching guides that can be used by teachers.Keyword: lexical meaning, contextual meaning, “Billboard Global 200,” song lyrics, pedagogical implication